2023
DOI: 10.3233/jad-230112
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Leisure Activities and Sleep Duration with Cognitive Function: A Nationwide Prospective Cohort Study of Chinese Old Adults

Abstract: Background: Leisure activities and sleep duration are correlated and have been linked to cognitive function, but most studies have examined only one of these factors. Objective: To investigate the independent and joint associations of leisure activities and sleep duration with cognitive function among older adults. Methods: We included 7,796 participants aged≥65 years from the Chinese Longitudinal Healthy Longevity Survey during 2008–2018 (waves 5–8). Self-reported leisure activities and sleep duration were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Finally, this study found that, compared to the older adult population who do not participate in any leisure activities, general health can serve as both a mediator and moderator of the impact of two types of leisure activities on survival status. On the one hand, participating in both types of leisure activities can help to comprehensively improve the physiological, psychological, and social adaptation dimensions of the health status of older adults, improve their quality of life, and reduce risk factors for death ( 35 , 36 ). On the other hand, good health can help strengthen the relationship between leisure activities and survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study found that, compared to the older adult population who do not participate in any leisure activities, general health can serve as both a mediator and moderator of the impact of two types of leisure activities on survival status. On the one hand, participating in both types of leisure activities can help to comprehensively improve the physiological, psychological, and social adaptation dimensions of the health status of older adults, improve their quality of life, and reduce risk factors for death ( 35 , 36 ). On the other hand, good health can help strengthen the relationship between leisure activities and survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also found that people with a total sleep duration of 7-8 h per day and a nocturnal sleep duration of 6-7 h are at the lowest risk of cognitive disorders (49). A national cohort study found that increased sleep duration among older adult people was independently associated with cognitive decline, and could be affected by gender and level of education (60). Therefore, subjective measurement of long sleep duration in elder people might be an important indicator for the risk of dementia.…”
Section: Comparison With Previous Workmentioning
confidence: 99%